Impact of Heroin and HIV on Gut Integrity and Immune Activation. (15th April 2022) - Hileman, Corrilynn O.; Bowman, Emily R.; Gabriel, Janelle; Kettelhut, Aaren; Labbato, Danielle; Smith, Cheryl; Avery, Ann; Parran, Theodore; Funderburg, Nicholas; McComsey, Grace A.
Abstract : Background: Altered gut integrity is central to HIV-related immune activation. Opioids may promote similar changes in gut permeability and/or increase systemic inflammation, potentially augmenting processes already occurring in people with HIV (PWH). Setting: Urban hospital systems in Cleveland, Ohio, and surrounding communities. Methods: This is a prospectively enrolled, cross-sectional study including people with and without HIV using heroin and people with and without HIV who have never used heroin, matched by age, sex, and CD4 + T-cell count (PWH only) to compare markers of gut integrity, microbial translocation, systemic inflammation, and immune activation. Results: A total of 100 participants were enrolled. Active heroin use was associated with higher concentrations of lipopolysaccharide-binding protein (LBP), beta-D-glucan (BDG), high-sensitivity C-reactive protein (hsCRP), soluble tumor necrosis factor-α-receptors I and II, soluble CD163, inflammatory monocytes, and activated CD4 + lymphocytes in adjusted models. HIV status tended to modify the effect between heroin use and LBP, BDG, hsCRP, patrolling monocytes, and activated CD4 + lymphocytes ( P < 0.15 for interactions); however, it was not as expected. The effect of heroin on these markers (except patrolling monocytes) was greatest among those without HIV rather than among those with HIV. Conclusions: Heroin use is associated with heightened microbial translocation, systemic inflammation, and immune activation. Concurrent HIV infection in virologically suppressed individuals does not seem to substantially worsen the effects heroin has on these markers.